Effects of intranasal oxytocin on fear extinction learning - Rashidi, Mahmoud; Simon, Joe J.; Bertsch, Katja; Wegen, Gerhard; Ditzen, Beate; Flor, Herta; Grinevich, Valéry; Wolf, Robert Christian; Herpertz, Sabine (Neuropsychopharmacology, 2025)
Once a threat no longer exists, extinction of conditioned fear becomes adaptive in order to reduce allotted resources towards cues that no longer predict the threat. In anxiety and stress disorders, fear extinction learning may be affected. Animal findings suggest that the administration of oxytocin (OT) modulates extinction learning in a timepoint-dependent manner, facilitating extinction when administered prior to fear conditioning, but impairing it when administered prior to extinction learning. The aim of the present study was to examine if these findings translate into human research. Using a randomized, double-blind, placebo-controlled, 2-day fear conditioning and extinction learning design, behavioral (self-reported anxiety), physiological (skin conductance response), neuronal (task-based and resting-state functional magnetic resonance imaging), and hormonal (cortisol) data were collected from 124 naturally cycling (taking no hormonal contraceptives) healthy females. When administered prior to conditioning (Day 1), OT, similar to rodent findings, did not affect fear conditioning, but modulated the intrinsic functional connectivity of the anterior insula immediately after fear conditioning. In contrast to animal findings, OT impaired, not facilitated, extinction learning on the next day and increased anterior insula activity. When administered prior to extinction learning (day 2), OT increased the activity in the bilateral middle temporal gyrus, and similar to animal findings, reduced extinction learning. The current findings suggest that intranasal OT impedes fear extinction learning in humans regardless of the timepoint of administration, providing new insights and directions for future translational research and clinical applications.